PI3Kγ mediates microglial proliferation and cell viability via ROS - Schmidt, Caroline; Schneble, Nadine; Lajqi, Trim; Wetzker, Reinhard; Müller, Jörg; Bauer, Reinhard (Cells, 2021)
Abstract: (1) Background: Rapid microglial proliferation contributes to the complex responses of the innate immune system in the brain to various neuroinflammatory stimuli. Here, we investigated the regulatory function of phosphoinositide 3-kinase γ (PI3Kγ) and reactive oxygen species (ROS) for rapid proliferation of murine microglia induced by LPS and ATP. (2) Methods: PI3Kγ knockout mice (PI3Kγ KO), mice expressing catalytically inactive PI3Kγ (PI3Kγ KD) and wild-type mice were assessed for microglial proliferation using an in vivo wound healing assay. Additionally, primary microglia derived from newborn wild-type, PI3Kγ KO and PI3Kγ KD mice were used to analyze PI3Kγ effects on proliferation and cell viability, senescence and cellular and mitochondrial ROS production; the consequences of ROS production for proliferation and cell viability after LPS or ATP stimulation were studied using genetic and pharmacologic approaches. (3) Results: Mice with a loss of lipid kinase activity showed impaired proliferation of microglia. The prerequisite of induced microglial proliferation and cell viability appeared to be PI3Kγ-mediated induction of ROS production. (4) Conclusions: The lipid kinase activity of PI3Kγ plays a crucial role for microglial proliferation and cell viability after acute inflammatory activation. Keywords: phosphoinositide 3-kinase γ; proliferation; cell viability; microglia; ROS; LPS; ATP